2016
DOI: 10.1016/j.cub.2016.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Activation of Rac1 Regulates the Forgetting of Object Recognition Memory

Abstract: Forgetting is a universal feature for most types of memories. The best-defined and extensively characterized behaviors that depict forgetting are natural memory decay and interference-based forgetting [1, 2]. Molecular mechanisms underlying the active forgetting remain to be determined for memories in vertebrates. Recent progress has begun to unravel such mechanisms underlying the active forgetting [3-11] that is induced through the behavior-dependent activation of intracellular signaling pathways. In Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
112
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 40 publications
14
112
1
Order By: Relevance
“…Increased activation of Rac1 in the mouse hippocampus through targeted expression of constitutively active mutant Rac1 accelerates decay of object-recognition memory by about 3-fold (Liu et al, 2016). Conversely, inhibition of Rac1 activity by expressing a dominant-negative mutant Rac1 significantly prolongs memory.…”
Section: The Neuroscience Of Active Forgettingmentioning
confidence: 99%
“…Increased activation of Rac1 in the mouse hippocampus through targeted expression of constitutively active mutant Rac1 accelerates decay of object-recognition memory by about 3-fold (Liu et al, 2016). Conversely, inhibition of Rac1 activity by expressing a dominant-negative mutant Rac1 significantly prolongs memory.…”
Section: The Neuroscience Of Active Forgettingmentioning
confidence: 99%
“…Our results showing impaired subsequent learning after a first learning experience in the absence of WT1 suggest that the first learning is more strongly represented; hence, the mechanisms that counteract memory strengthening and consolidation normally are critical for 20 The authors declare no competing interests. Himmelreich…”
Section: Discussionmentioning
confidence: 85%
“…A key question is whether consolidated memories are weakened through a passive decay process, and/or by a learning-induced, active mechanisms that serves to promote memory flexibility. In other words, do signaling pathways that are activated during experience not only support consolidation, but also include counteracting molecular regulators that can decrease memory strength and favor forgetting 6 , such as the Rho family of GTPases signaling G proteins (Rac) [18][19][20] , scribble scaffolds 21 , DAMB dopamine receptors 22 , inhibition of AMPA receptor recycling 23,24 , and neurogenesis 5,25 ?…”
Section: Main Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, just as an increase in the number of AMPA receptors in the postsynaptic membrane is associated with increased memory, a decrease in this number via AMPA receptor endocytosis has recently been associated with forgetting [31]. Other work has shown that natural forgetting involves a protein called Rac [32, 33]—overexpression of Rac accelerates forgetting, and inhibition extends memory. On a longer timescale (thus less relevant to our work, but still interesting), another contributor to transience is hippocampal neurogenesis: the generation of neurons from stem cells in the dentate gyrus region of the hippocampal formation [34, 35].…”
Section: Introductionmentioning
confidence: 99%